"How bona does fides need to be in contracts of Marine insurance?"a comparative analysis of the English and the South African approach to Marine insurance contracts - Cohen,JC (Institute of Marine and Environmental Law, 2023)
The English Law of Marine Insurance embraces the concept of Utmost Good Faith ( Uberrimae Fide,). The underlying motive for this is apparent in the requirement that an even higher standard of honesty than usual is necessary. The reason for this is that circumstances of a special nature exist which put the insurer at a far greater risk and at the mercy of the assured's1 preparedness to disclose facts of a material nature.